2013
DOI: 10.5152/akd.2013.100
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical left ventricular systolic dysfunction in patients with mild-to-moderate rheumatic mitral stenosis and normal left ventricular ejection fraction: an observational study

Abstract: Subclinical left ventricular systolic dysfunction in patients with mild-to-moderate rheumatic mitral stenosis and normal left ventricular ejection fraction: an observational studyHafif orta derecede romatizmal mitral kapak darlığı ve normal sol ventrikül ejeksiyon fraksiyonu olan hastalarda subklinik sol ventrikül sistolik disfonksiyonu: Bir gözlemsel çalışma Original Investigation Özgün Araşt›rma 328ÖZET Amaç: Tanı ve tedavideki gelişmelere rağmen mitral kapak darlığı (MD) genç erişkinlerde morbiditenin önem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Moreover, a positive correlation was found between MVA and impaired longitudinal strain rates ( 18 ) . However, these results are not consistent in patients with mild to moderate MS ( 15 , 19 ) .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, a positive correlation was found between MVA and impaired longitudinal strain rates ( 18 ) . However, these results are not consistent in patients with mild to moderate MS ( 15 , 19 ) .…”
Section: Discussionmentioning
confidence: 72%
“…LVEF has limitations for defining the degree of systolic ventricular dysfunction ( 14 ) . Echocardiographic assessment with speckle tracking echocardiography has demonstrated that longitudinal and circumferential strain rates are globally diminished in MS patients ( 15 ) , even with preserved EF.…”
Section: Discussionmentioning
confidence: 99%